PENGARUH PENGGUNAAN TRAKTOR TERHADAP TEGAKAN TINGGAL PADA BEBERAPA PENGUSAHAAN HUTAN DI KALIMANTAN TIMUR - Jurnalis Thaib (Jurnal Penelitian Hasil Hutan, 1985)
The  damage  to  residual stands  as a  result  of  tractor  logging is evaluated.  In 10 concessions  in East Kalimantan, the number of  trees felled  per  hectare  was corelated with the percent  decrease in the number of residual trees (20 cm and up) per hectare.The  results  indicated  that  increasing  the number  of trees felled per hectare caused greater decrease in the percentage of  residual  trees (20 cm and up).A better logging plan including strict adherence to the TPI (Indonesian  Selective  Logging)  regulations, pre-laid skidding  roads and  tree  location  plan is recommended to reduce the  damage to residual stands.